A systematic revision of Calotes Cuvier, 1817 (Squamata: Agamidae) from the Western Ghats adds two genera and reveals two new species - Pal, Saunak; Vijayakumar, S.p.; Shanker, Kartik; Jayarajan, Aditi; Deepak, V. (Zootaxa, 2018)
Lizards of the genus Calotes are geographically restricted to South Asia, Indo-China and parts of Southeast Asia. The greatest diversity of the genus is from the biodiversity hotspots in South Asia: Western Ghats (Peninsular India), Sri Lanka and Indo-Burma. Here, we present a systematic revision of members of the genus Calotes from Peninsular India using a combination of molecular phylogeny, geographical distribution and morphological characters. We show that Calotes from the Western Ghats is paraphyletic and consists of three major clades, one of which is widely distributed in South and Southeast (SE) Asia, while the others are restricted to Peninsular India. The Peninsular Indian clade is composed of two sister clades: Psammophilus, with a wider distribution and a second clade, composed of two extant species, Calotes rouxii and Calotes ellioti and two new species, all restricted to the Western Ghats region. Based on morphological differences, we retain the generic status of Psammophilus and assign its sister clade to a new genus Monilesaurus gen. nov. and transfer the following species, C. rouxii and C. ellioti, to this new genus. We also provide diagnoses and descriptions for two new species recognized within Monilesaurus gen. nov. In addition, Calotes aurantolabium from the Western Ghats was observed to be deeply divergent and to share a sister-relationship with the clade composed of Calotes, Monilesaurus gen. nov., and Psammophilus. Based on its phylogenetic position and morphological attributes, we assign this species to a new genus Microauris gen. nov. These new discoveries highlight the evolutionary significance of the Western Ghats in housing novel lizard diversity.